Affective and cognitive predictors of affective response to exercise: Examining unique and overlapping variance. (November 2016) - Sala, Margarita; Baldwin, Austin S.; Williams, David M.
Abstract: Objectives: Affective response to exercise has been suggested as an important factor in determining regular exercise. However, it is unclear the extent to which anticipatory affect factors (affective attitudes, implicit associations, and affective associations), anticipated affect factors (anticipated regret, anticipated pride), and cognitive factors (self-efficacy, intentions) explain overlapping or unique variance in affective response to exercise. Design: We systematically examined the extent to which these various affective and cognitive factors relevant to exercise predict affective response, and determined the extent to which these factors account for unique or overlapping variance in affective response. Method: Healthy young adults (N = 69) completed measures of affective attitudes, affective associations, implicit associations, anticipated affect, self-efficacy, and exercise intentions. Participants then exercised for 20-min at moderate intensity on a treadmill, during and after which they reported their affective response. Using variables that were independent predictors, we conducted multivariate analyses to determine which factors account for unique variance in affective response to exercise. Results: In three of four multivariate models, both anticipated and anticipatory affect variables explained unique variance in affective response during exercise. Only anticipatory affect variables accounted for unique variance in affective response immediately post-exercise. Finally, the association between exercise self-efficacy and affective response during-exercise was rendered non-significant after controlling for affective factors in all three multivariate models. Conclusions: The unique associations between affective response to exercise and affective, but not cognitive, factors elucidate key predictors of affective response during- and post-exercise. Highlights: Anticipated and anticipatory affect both predict affective response in-exercise. Anticipatory affect predicts affective response immediately post-exercise. Self-efficacy fails to predict affective response beyond the affective factors.